2018
DOI: 10.1111/cea.13262
|View full text |Cite
|
Sign up to set email alerts
|

House dust mite‐driven neutrophilic airway inflammation in mice with TNFAIP3‐deficient myeloid cells is IL‐17‐independent

Abstract: These findings show that neutrophilic airway inflammation induced by activated TNFAIP3/A20-deficient myeloid cells can develop in the absence of IL-17RA-signalling. Neutrophilic inflammation is likely maintained by similar quantities of pro-inflammatory cytokines IL-1β and IL-6 that can, independently of IL-17-signalling, induce the expression of neutrophil chemo-attractants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Several studies have shown that IL-17 contributes to the development of airway inflammation and AHR in wild-type mice ( 45 48 ). Reported IL-17 levels were elevated in homogenized lung tissue; however, the values were not corrected for total protein in these studies ( 45 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that IL-17 contributes to the development of airway inflammation and AHR in wild-type mice ( 45 48 ). Reported IL-17 levels were elevated in homogenized lung tissue; however, the values were not corrected for total protein in these studies ( 45 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IL-17 contributes to the development of airway inflammation and AHR in wild-type mice ( 45 48 ). Reported IL-17 levels were elevated in homogenized lung tissue; however, the values were not corrected for total protein in these studies ( 45 48 ). We reported previously that IL-17 was present in saline and HDME wild-type groups, and the levels were elevated in Arg2 -deficient mice ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Newborns with asthma at school age had reduced A20 expression at birth, suggesting A20 as a possible biomarker predicting subsequent asthma [ 10 ]. A20 can also regulate T helper 2-mediated eosinophilic and neutrophilic airway inflammation via pulmonary conventional type 1 Langerin-expressing dendritic cells and myeloid cells, respectively [ 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous mechanistic‐based studies have revealed a role for ubiquitin‐modifying enzyme TNFAIP3 (TNFa‐induced protein 3, also known as A20) in the modulation of CD4+ IL‐17+ T cells and myeloid cell–driven pulmonary neutrophil inflammation . TNFAIP3 expression in DCs is required for house dust mite (HDM)–specific TH17 cell differentiation through expression of the Th17‐instructing cytokines IL‐1β, IL‐6 and IL‐2314.…”
Section: Experimental Models Of Allergic Diseasementioning
confidence: 99%